Plus-sized misadventures in love! 2 - Mamakari (Plus-Sized Misadventures in Love!, 2025)
Plus-Sized Misadventures in Love, Volume 2 is the next installment in this new breakout manga series perfect for fans of A Silent Voice and Perfect World! All Yumeko ever saw were her flaws. Her unhappy outlook infected not just her, but everyone around her, too. It's only after a car accident that leaves Yumeko with amnesia that she wakes up with a brand-new lease on life, one that attracts all kinds of adventures and maybe even love.